Land use and climatic factors structure regional patterns in soil microbial communities - Drenovsky, Rebecca E.; Steenwerth, Kerri L.; Jackson, Louise E.; Scow, Kate M. (Global ecology and biogeography, 2010)
Although patterns are emerging for macroorganisms, we have limited understanding of the factors determining soil microbial community composition and productivity at large spatial extents. The overall objective of this study was to discern the drivers of microbial community composition at the extent of biogeographical provinces and regions. We hypothesized that factors associated with land use and climate would drive soil microbial community composition and biomass. Great Basin Province, Desert Province and California Floristic Province, California, USA. Using phospholipid fatty acid analysis, we compared microbial communities across eight land-use types sampled throughout the State of California, USA (n= 1117). The main factor driving composition and microbial biomass was land-use type, especially as related to water availability and disturbance. Dry soils were more enriched in Gram-negative bacteria and fungi, and wetter soils were more enriched in Gram-positive, anaerobic and sulphate-reducing bacteria. Microbial biomass was lowest in ecosystems with the wettest and driest soils. Disturbed soils had less fungal and more Gram-positive bacterial biomass than wildland soils. However, some factors known to influence microbial communities, such as soil pH and specific plant taxa, were not important here. Distinct microbial communities were associated with land-use types and disturbance at the regional extent. Overall, soil water availability was an important determinant of soil microbial community composition. However, because of the inclusion of managed and irrigated agricultural ecosystems, the effect of precipitation was not significant. Effects of environmental and management factors, such as flooding, tillage and irrigation, suggest that agricultural management can have larger effects on soil microbial communities than elevation and precipitation gradients.